The contribution of mast cells to bacterial and fungal infection immunity. Issue 1 (12th February 2018) - Piliponsky, Adrian M.; Romani, Luigina
Summary: Mast cells are hematopoietic progenitor‐derived, granule‐containing immune cells that are widely distributed in tissues that interact with the external environment, such as the skin and mucosal tissues. It is well‐known that mast cells are significantly involved in IgE‐mediated allergic reactions, but because of their location, it has also been long hypothesized that mast cells can act as sentinel cells that sense pathogens and initiate protective immune responses. Using mast cell or mast cell protease‐deficient murine models, recent studies by our groups and others indicate that mast cells have pleiotropic regulatory roles in immunological responses against pathogens. In this review, we discuss studies that demonstrate that mast cells can either promote host resistance to infections caused by bacteria and fungi or contribute to dysregulated immune responses that can increase host morbidity and mortality. Overall, these studies indicate that mast cells can influence innate immune responses against bacterial and fungal infections via multiple mechanisms. Importantly, the contribution of mast cells to infection outcomes depends in part on the infection model, including the genetic approach used to assess the influence of mast cells on host immunity, hence highlighting the complexity of mast cell biology in the context of innate immune responses.